Assessing the awareness and practice of Hospital Acquired Infections (HAIs) among nursing staff of Civil Hospital, Rajkot, Gujarat, India - Sheth, Ankit M.; Jani, Darshan S.; Rangoonwala, Matib M.; Kadri, Amiruddin M. (International Journal of Research in Medical Sciences, 2017)
Background:With advances in health care system, threat to Hospital Acquired Infections (HAIs) still remains. HAIs continue to affect hospitalized patients and results in morbidity, mortality and additional costs. Health care workers, especially nurses can play critical role in prevention and control of HAIs. The purpose was to study their awareness regarding HAIs and practice towards prevention and control measures. Methods: It was a cross sectional study conducted in Civil Hospital, Rajkot from October 2014 to December 2014. Out of total 184 staff nurses, 92 (50% of the total following convenient sampling) were selected. A list of all staff nurse was made alphabetically and every alternate nurse was selected for interview. Of the 92 staff nurses approached, 83 consented and gave complete response. Interview was conducted using a pretested semi structured questionnaire and analysis was done using Excel 2007. Results:80 (93.02%) participants had heard about HAIs. More than half (60.4%) of the participants acknowledged that urinary and respiratory tract infections were the two most common HAIs. 52 (60.4%) of the participants acknowledged that direct skin to skin contact and improper handling of bio medical waste were the two most common modes of transmission of HAIs. 47 (56.6%) practiced hand washing before and after surgical procedures. 30 (36.1%) participants had ‘good’ knowledge regarding HAIs. Conclusions:The present study showed that level of awareness and practice regarding HAIs among nursing staff was average. Considering the important role of nurses in HAIs, there is a need to develop a system of continuous education to increase nurses’ awareness and hence adopt appropriate health behaviours and increase adherence to precautions.